Effect of Wellbeing on Job Satisfaction and Burnout Among the Employees in DepEd Division of Northern Samar - Froilan, Michael J.; Dapulag-Enano, Elna; Bobiles, Peter R.; Orias Jr., Roberto T.; Saldo Jr., Pepito E.; Donoga, Danhill C. (International Journal of Research in Interdisciplinary Studies, 2026)
This study examined the effect of wellbeing on job satisfaction and burnout among employees in the Department of Education (DepEd) Division of Northern Samar, Philippines, focusing on how multiple dimensions of wellbeing predict positive and negative work-related outcomes across teachers, non-teaching personnel, school heads, and supervisors. Using a quantitative, predictive–correlational design, the study was conducted during the School Year 2024–2025 and involved 1,956 DepEd employees selected through stratified sampling to ensure representation across position categories. Data were gathered using a structured survey questionnaire covering respondents’ profile, multidimensional wellbeing (physical, social, emotional, spiritual, intellectual, financial, environmental, and occupational), burnout, and job satisfaction. Wellbeing was measured using an instrument adapted from Rebolo and Constantino (2020), burnout was assessed using the 15-item Burnout Assessment Tool by Schaufeli et al. (2020), and job satisfaction was evaluated across four domains. Multiple regression analysis at the 5% level of significance was employed to determine the predictive effects of wellbeing on job satisfaction and burnout. Results indicated that wellbeing significantly predicted job satisfaction, explaining 29.4% of its variance, with physical, social, financial, environmental, and occupational wellbeing showing significant positive effects, and occupational wellbeing emerging as the strongest predictor. Wellbeing also significantly predicted burnout, accounting for 9.6% of the variance. Social, spiritual, environmental, and occupational wellbeing exhibited significant inverse relationships with burnout, indicating protective effects, whereas intellectual wellbeing demonstrated a positive association with burnout, suggesting that heightened cognitive demands may intensify strain when insufficiently supported. Overall, the findings established that wellbeing is a critical organizational resource influencing both job satisfaction and burnout among DepEd employees, underscoring the need for a holistic, systems-oriented wellbeing framework in public education, particularly in geographically and resource-constrained divisions, to sustain a resilient and effective workforce.